Construction of cuproptosis-related gene signature to predict the prognosis and immunotherapy efficacy of patients with bladder cancer through bioinformatics analysis and experimental validation - Liu, Zijian; Zhu, Fubin; Zhang, Pu; Qian, Bei; Liu, Weihui; Xiao, Yajun; Chen, Nianyong; He, Qingliu; Xiao, Jianghong (Frontiers in Genetics, 2022)
Abstract Background: A new form of cell death, copper-dependent cell death (termed cuproptosis), was illustrated in a recent study published in Science. However, the role of cuproptosis in bladder cancer (BLCA) remains unknown. Materials and Methods: Sequencing data obtained from BLCA samples in TCGA and GEO databases were preprocessed for analysis. Biological function and immune cell infiltration levels evaluated by GSVA were employed to calculate enrichment scoress. Iteration LASSO and COX regression model was employed to select feature genes and construct a novel cuproptosis-related (CR) scoress signature. GDSC and TIDE analysis was used to predict the chemotherapy and immunotherapy efficacy for BLCA patients. The relative expression of the genes involved in the signature was also clarified by real-time quantitative PCR in cell lines and tissues. Results: Expression abundance and prognostic value of cuproptosis regulators proved cuproptosis might play a vital part in the carcinogenesis of BLCA. GSVA revealed that cuproptosis regulators might be associated with metabolism and metastasis-related pathways, such as TGF-β, protein secretion, oxidative Phosphorylation, MYC targets, MTORC1 and adipogenesis pathways. CR scoress could predict the prognosis and evaluate the chemotherapy and immunotherapy efficacy of BLCA. CR scoress was positively correlated with EMT, MYC, MTORC1, HEDGEHOG, and E2F signaling pathways, meanwhile negatively correlated with several immune cells infiltration levels, such as CD8+ T cells, γδT cells, and activated dendritic cells. Several GEO datasets were used to validate the power of prognostic prediction, and a nomogram was also established for clinical use. The expression of DDX10, RBM34, RPL17 were significantly higher in BLCA cell lines and tissues in comparison with that in corresponding normal controls. Conclusion: Cuproptosis might play an essential role in the progression of BLCA. CR scoress could be helpful in the investigation of prognostic prediction and therapeutic efficacy and could make contributions to further studies in BLCA.